Disentangling the Association Between Government Debt and Economic Growth: A Granger Causality Approach from Indonesia - Rosdiana Sijabat (Jurnal Studi Pemerintahan, 2020)
This paper aims to examine the possible Granger-causality relationship between public debt and economic growth in Indonesia between 1998 and 2018. To accomplish this aim, a time series regression approach as well as diagnostic tests such as the Augment Dickey–Fuller test and Johansen cointegration test (which provides evidence of a long-term relationship between external debt and economic growth) were conducted. A VECM Granger causality approach was chosen to investigate the causal link between government and economic growth. The VECM estimation provides new evidence that, over the long term, domestic debt has significantly and positively affected economic growth; at the same time, external debt has significantly and negatively affected economic growth. Meanwhile, Granger-causality analysis shows that economic growth has a unidirectional causal relationship with external public debt, but does not have such a relationship with domestic public debt. For this study, a series of 20 data points per variable were analyzed, covering 1998 through 2018. This sample size is rather small, and as such its findings are not perfect. The use of a much larger data set would enhance any similar studies in the future. Nonetheless, this study illuminates the role of government debt in the economy by highlighting the importance of domestic markets as sources of public debt to promote economic growth in Indonesia, and recommends that the government do so.